Map of part of the province of Manitoba and North West Territories shewing the Hudsons Bay Company's sections [part 1] - Dennis, John Stoughton (Surveyor); Burland Lithographic Company (Lithographer) (Hudson's Bay Company, 1881)
This is a map of land distribution in Manitoba and the Northwest Territories in 1881. It consists of two parts: part 1 - general map of the region; and part 2 - inset maps of major cities and towns, as well as Hudson's Bay Company's information on cities, farming, lands, climate, municipal organization, schools, timber and fuel industries, transportation and communication in Manitoba and the Northwest Territories [see also record for part 2]. Shows Dominion lands, Hudson's Bay Company's lots, railways, Indian reserves, citties and towns. Scale 1:506,880, or 1 inch to 8 miles. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .